ANALYSIS OF FACTORS AFFECTING THE TIMING OF PATIENTS SEEKING MEDICAL CARE IN ACUTE CORONARY SYNDROME WITH ST-SEGMENT ELEVATION - Солопова, Юлия Александровна; Огарков, Михаил Юрьевич; Янкин, Артем Юрьевич; Гущин, Юрий Григорьевич; Шулакова, Марина Александровна; Марешин, Евгений Николаевич; Шахшнейдер, Надежда Михайловна; Горелкина, Ольга Анатольевна (Medicine in Kuzbass, 2019)
Subject of research. Time «pain-call ambulance».Object of study. A continuous sample of patients with acute coronary syndrome (ACS) with SТ segment elevation (ACS PST) admitted to the regional vascular center of Novokuznetsk in 2016.Purpose of research – to identify the factors affecting the timeliness of emergency medical care in patients with ACS РSТ.Methods. A questionnaire, a copy of the primary medical documentation. Statistical method to identify significant differences between the two groups using the Mann-Whitney test. The critical level of significance in testing statistical hypotheses in this study was taken to be 0.05.Main results. The influence of sex and age on the time of emergency medical service (NSR) is analyzed. The influence of coronary and family history on the time of the SMP brigade call is traced. The influence of the presence of a cell phone on the time of the call and the ability to independently call the NSR on the cell phone in the event of symptoms of ACS are analyzed.Application of the results. Cardiology, health care organization, sociology.Conclusions. Factors that increase the time from ACS symptoms to NSR are male sex and senile age. For this group of people needs social advertising about the necessity of early challenge SMP, because early referral for medical assistance reduces the delay time of revascularization and reduced mortality. Patients with a history of angina pectoris before myocardial infarction, cause SMP significantly earlier than patients without previous coronary history.
Keywords: acute coronary syndrome; time to call an ambulance; «pain – call» time; revascularization